To determine which expression is equivalent to \(9x^2 - 25\), we can recognize that this expression is a difference of squares. The difference of squares can be factored using the formula:
\[ a^2 - b^2 = (a + b)(a - b) \]
Here \(a^2\) is \(9x^2\) and \(b^2\) is \(25\).
- Identify \(a\) and \(b\):
- \(a = 3x\) (since \( (3x)^2 = 9x^2 \))
- \(b = 5\) (since \(5^2 = 25\))
Now, using the difference of squares formula: \[ 9x^2 - 25 = (3x + 5)(3x - 5) \]
Now we can evaluate the choices provided:
- (4.5x + 12.5)(4.5x - 12.5): This does not match our expression.
- (3x + 5)^2: This is a perfect square, not a difference of squares.
- (3x + 5)(3x - 5): This matches our earlier conclusion: \(9x^2 - 25\) can be factored as this.
- 9x(x - 25): This does not represent the original expression correctly.
Thus, the equivalent expression is:
(3x + 5)(3x - 5).